2018
DOI: 10.1111/ced.13641
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of Trichophyton rubrum in tinea unguium after itraconazole therapy in vivo observed using scanning electron microscopy

Abstract: Summary Background Tinea unguium is a dermatophyte infection of the nails. Itraconazole is a broad‐spectrum antifungal drug used to treat this disease. It works by interfering with the synthesis of ergosterol in the cell membrane, thus causing changes that can be seen under scanning electron microscopy (SEM). Aim To observe under SEM the in vivo ultrastructural changes of tinea unguium caused by Trichophyton rubrum before and after itraconazole (ICZ) therapy, and to explore the in vivo antifungal effect of ICZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…On the basis of the published study on the effect of terbinafine on the morphology of Trichophyton rubrum, in our research, the morphological observations by SEM exhibited that treatment with EA and SK showed significant morphological changes, including hyphae appearing with rough and swollen surface, mycelium dry deformation and expansion, many fracture, visible surface peeling, mycelia rupture, mushy, and cell content overflow. e majority of T. rubrum hyphae were dry, shrivelled, curved, and folded (Figure 3) and in accordance with the previous report [26]. e shrinkage, flattening, bending, and twisting of the hyphae with wrinkled surface after application for 7 days were also identical to the morphological changes in hyphae cultured with luliconazole [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the basis of the published study on the effect of terbinafine on the morphology of Trichophyton rubrum, in our research, the morphological observations by SEM exhibited that treatment with EA and SK showed significant morphological changes, including hyphae appearing with rough and swollen surface, mycelium dry deformation and expansion, many fracture, visible surface peeling, mycelia rupture, mushy, and cell content overflow. e majority of T. rubrum hyphae were dry, shrivelled, curved, and folded (Figure 3) and in accordance with the previous report [26]. e shrinkage, flattening, bending, and twisting of the hyphae with wrinkled surface after application for 7 days were also identical to the morphological changes in hyphae cultured with luliconazole [27].…”
Section: Discussionsupporting
confidence: 90%
“…e results show that EA and SK are able to exert an efficient dose-dependent inhibitory activity on T. rubrum in vitro. Evidence-Based Complementary and Alternative Medicine Although a few researchers observed ultrastructural changes of Trichophyton rubrum after itraconazole therapy and terbinafine therapy observed using SEM [26], the structural changes of T. rubrum after EA and SK treatment in vitro have not been reported previously. On the basis of the published study on the effect of terbinafine on the morphology of Trichophyton rubrum, in our research, the morphological observations by SEM exhibited that treatment with EA and SK showed significant morphological changes, including hyphae appearing with rough and swollen surface, mycelium dry deformation and expansion, many fracture, visible surface peeling, mycelia rupture, mushy, and cell content overflow.…”
Section: Discussionmentioning
confidence: 96%